2001
DOI: 10.5144/0256-4947.2001.283
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Cholesteryl Esters and Other Lipids in the Plasma of Patients with End-Stage Renal Failure

Abstract: Background:The importance of plasma lipid abnormalities in chronic renal failure (CRF) is well recognized, but surprisingly little attention has been given to the study of some plasma lipid fractions, including cholesteryl esters (CE) and phospholipids, which might be expected to be important factors in the pathogenesis of the disease. Materials and Methods: Fasting blood samples were taken from 25 control subjects and 53 CRF patients (29 predialysis and 24 on hemodialysis). Samples were analyzed for urea nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
(33 reference statements)
2
8
0
Order By: Relevance
“…Our research showed that 3 lysoPC species are downregulated in the IPD and T2DM groups, possibly owing to low activity of phospholipase A2, which catalyzes PC hydrolysis to lysoPC. Alternatively, these changes are related to deficiency of lecithin-cholesterol acyltransferase (27 ). Consistent with our findings, recent studies have shown that decreased concentrations of lysoPC(18:2) are associated with increased risk of T2DM (12,19 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our research showed that 3 lysoPC species are downregulated in the IPD and T2DM groups, possibly owing to low activity of phospholipase A2, which catalyzes PC hydrolysis to lysoPC. Alternatively, these changes are related to deficiency of lecithin-cholesterol acyltransferase (27 ). Consistent with our findings, recent studies have shown that decreased concentrations of lysoPC(18:2) are associated with increased risk of T2DM (12,19 ).…”
Section: Discussionsupporting
confidence: 91%
“…1, but the increase was not significant. All of these changes are consistent with those previously reported from this laboratory, 15,16 but not necessarily with those reported in other studies. [11][12][13][14][17][18][19][20] Clearly, further studies on the significance, in uremia, of changes in the cholesterol content of all lipoprotein classes, including VLDL, are needed in order to understand the risks of vascular disease and other potential problems in such patients.…”
Section: Discussionsupporting
confidence: 93%
“…Our results show that lysophosphatidylcholine is obviously decreased in CRF patients, and the reason is not clear. It could be presumed that the toxins in the body inhibits the activity of phospholipase A2 and make the decrease of LPC generation; or, the changes noted appear to be consequences of or related to deficiency of the serum enzyme lecithin-cholesterol acyltransferase (Gillett et al 2001). However, lysophosphatidylcholine can mediate many cell signaling in monocytes/macrophages (Duong et al 2004) and specific receptors (Oestvang and Johansen 2006), so that it participates in inflammatory response.…”
Section: Resultsmentioning
confidence: 99%